Magnetic Resonance Comparison of Left-Right Heart Volumetric and Functional Parameters in Thalassemia Major and Thalassemia Intermedia Patients. (2nd April 2015) - Liguori, Carlo; Pitocco, Francesca; Di Giampietro, Ilenia; De Vivo, Aldo Eros; Schena, Emiliano; Giurazza, Francesco; Sorrentino, Francesco; Zobel, Bruno Beomonte
Abstract : Objectives . To evaluate a population of asymptomatic thalassemia major (TM) and thalassemia intermedia (TI) patients using cardiovascular magnetic resonance (CMR). We supposed that TI group could be differentiated from the TM group based on T 2 ∗ and that the TI group could demonstrate higher cardiac output. Methods . A retrospective analysis of 242 patients with TM and TI was performed (132 males, 110 females; mean age 39.6 ± 8 years; 186 TM, 56 TI). Iron load was assessed by T 2 ∗ measurements; volumetric functions were analyzed using steady-state-free precession sequences. Results . Significant difference in left-right heart performance was observed between TM with iron overload and TI patients and between TM with iron overload and TM without iron overload (P < 0.05 ); no significant differences were observed between TM without iron overload and TI patients. A significant correlation was observed between T 2 ∗ and ejection fraction of right ventricle- (RV-) ejection fraction of left ventricle (LV); an inverse correlation was present among T 2 ∗ values and end-diastolic volume of LV, end-systolic volume of LV, stroke volume of LV, end-diastolic volume of RV, end-systolic volume of RV, and stroke volume of RV. Conclusions . CMR is a leading approach for cardiac risk evaluation of TM and TI patients.